2017
DOI: 10.1161/jaha.116.004803
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cardiovascular Disease by the Framingham‐REGICOR Equation in the High‐Risk PREDIMED Cohort: Impact of the Mediterranean Diet Across Different Risk Strata

Abstract: BackgroundThe usefulness of cardiovascular disease (CVD) predictive equations in different populations is debatable. We assessed the efficacy of the Framingham‐REGICOR scale, validated for the Spanish population, to identify future CVD in participants, who were predefined as being at high‐risk in the PREvención con DIeta MEDiterránea (PREDIMED) study—a nutrition‐intervention primary prevention trial—and the impact of adherence to the Mediterranean diet on CVD across risk categories.Methods and ResultsIn a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In a model adjusted for confounding factors, the “Healthy” pattern was associated to low occurrence of abdominal obesity, dyslipidemia, diabetes, and hypertension. This pattern resembles other cardioprotective patterns described in the literature and associated with low disease risk [15, 51, 52] and low mortality [5355]. Therefore, the protective effect of this pattern is well established.…”
Section: Discussionsupporting
confidence: 83%
“…In a model adjusted for confounding factors, the “Healthy” pattern was associated to low occurrence of abdominal obesity, dyslipidemia, diabetes, and hypertension. This pattern resembles other cardioprotective patterns described in the literature and associated with low disease risk [15, 51, 52] and low mortality [5355]. Therefore, the protective effect of this pattern is well established.…”
Section: Discussionsupporting
confidence: 83%
“…However, our results indicate that the presence of dyslipidemia was associated with a higher aMED score. Scientific studies published about this issue found that the MedDiet reduces the risk of T2D improving postprandial lipemia, lipid profile, and cardiovascular risk factors [3,4,[38][39][40][41][42][43]. Our results could be due to the fact that participants with dyslipidemia may have received specific dietary counselling based on the MedDiet to improve their lipid profile.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, WHtr and ABSI are the best anthropometric parameters according to FR and SCORE charts for Spanish males, while WHtr, WC and ABSI demonstrate better correlation with CVR according to the ACC/AHA chart. It is noticeable that several CVR studies have been carried out in the Spanish population (IBERICA, DORICA, PREDIMED amongst others) [3537], but the correlation of anthropometric parameters with the CVR has not been yet studied. Nevertheless, some international studies have contributed to study the relationship between anthropometric indexes and the prediction of cardiovascular events, metabolic variables and total mortality, in a diversity of populations.…”
Section: Discussionmentioning
confidence: 99%